Strategi Pengembangan Wisata Halal Pantai Pangubaian Kabupaten Kaur Dengan Metode Analytical Hierarcy Process - Puspita, Della; Sunarto, Andang; Hasanah, Uswatun (Indonesian Journal of Islamic Economics and Business, 2024)
The purpose of this research is to determine the existence of tourism, a country or more specifically the local government where the tourist attraction is located receives income from the income of each tourist attraction. Halal tourism, as defined by this concept, considers Islamic law when deciding on tourism products as well as tourism services, criteria and alternatives that are priorities in determining strategies for developing halal tourism at Pengubaian Beach. To test this, researchers used a quantitative approach with primary data collection techniques in the form of questionnaires distributed to 85 respondents. The data analysis technique used is the Analytical Hierarchy Process method using the Expert Choice 11 program. From the results of the research and discussion it is known that the attractiveness criterion is the priority criterion with the highest weight value, namely 0.348. And alternative natural tourism in the attractiveness criteria with a weighted value of 0.845